Análise comparativa dos conversores estáticos forward e flyback para o balanceamento de células em pacotes de baterias de veículos híbridos e elétricos - Okida, Luiz Haruki (2024)
This work aims to compare the topologies of static electrical energy converters Flyback and Forward operating in Discontinuous Conduction Mode (DCM) to balance a battery pack of a hybrid or electric vehicle formed with four cells. Balancing the battery pack increases the performance and durability of the energy storage system. The methodology of this work follows the development of four power specifications: 25 W, 50 W, 75 W, and 100 W, with input and output voltage equal to 48 V, and compares them as a function of balancing time and electrical efficiency. At the end of this work, the simulation and practical test are presented, where it is verified that the Flyback converter can perform the balancing.